Los robots en el sector servicios - Polastri Roque, Rodrigo Alonso (2020)
This research details one of the applications that robots have nowadays in the service sector. Within this sector, specifically in the hotel industry, there is a trend towards the use of robots and artificial intelligence to generate new experiences for its users. Furthermore, the research details the interaction that robots have in this sector and the opportunities that they offer to companies in order to improve their customers’ satisfaction through an increase in productivity, quality and speed of service. In order to achieve this, a consultant specialized in artificial intelligence and data science was interviewed, in addition to the collection of experts’ opinions, testimonials and success cases in relation to the use of robots in the hotel industry. One of the most representative examples is the one of the Hilton chain, which introduced a robot as part of the concierge in one of its hotels in the United States. This is a success story in which the hotel chain achieved an increase in indicators such as the queue time and concierge productivity after the implementation. Nevertheless, the research concludes that the introduction of this technology in the sector is not a threat to human workers, but rather a support for them to perform higher value tasks.